2012
DOI: 10.1007/s00134-012-2476-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the sublingual microcirculation and endothelial adhesion molecules during the course of severe meningococcal disease treated in the paediatric intensive care unit

Abstract: Microcirculatory dysfunction is present in children with severe MCD with improvement alongside clinical recovery. Microcirculatory dysfunction correlated with markers of endothelial activation. Sublingual SDF imaging is feasible in children ventilated on PICU for severe sepsis and may prove useful in studies assessing illness severity and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 32 publications
2
30
0
3
Order By: Relevance
“…However, of potential relevance to the present data is the observation that there is abnormal sublingual microcirculatory density and function in pediatric sepsis (25,26), which may be exacerbated by the microvascular sequestration of P. falciparum (27) in malaria. These factors might have attenuated the buccal absorption of ArTiMist in our children but may not have been influential in the upper small intestine.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, of potential relevance to the present data is the observation that there is abnormal sublingual microcirculatory density and function in pediatric sepsis (25,26), which may be exacerbated by the microvascular sequestration of P. falciparum (27) in malaria. These factors might have attenuated the buccal absorption of ArTiMist in our children but may not have been influential in the upper small intestine.…”
Section: Discussionmentioning
confidence: 72%
“…There were 16 patients recruited to study 1 who received ArTiMist, but one was withdrawn after the second dose due to a protocol violation (incorrect drug storage). In study 2, a total of 76 patients were allocated to ArTiMist from the three sites (27,25, and 24 children from Rwanda, Ghana, and Burkina Faso, respectively). All patients responded to ArTiMist with prompt parasite clearance (median parasite clearance time in both studies, 24 h), and there were no treatment-related serious adverse events (data not shown).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The authors concluded that inadequate or suppressed shedding during sepsis might be associated with increased mortality, and they hypothesize that the shedding process is indeed protective for the host. Similarly, in a large pediatric ICU study on microcirculatory dysfunction in meningococcal sepsis in children, levels of sE-selectin, sVCAM-1 and sICAM-1,but not sP-selectin, were significantly increased in septic patients but negatively correlated with the degree of microcirculatory dysfunction (a measure of sepsis severity), as assessed by sublingual imaging [36].…”
Section: Soluble Adhesion Moleculesmentioning
confidence: 89%
“…There were negative correlations between the ICAM-1, VCAM-1, E-selectin levels and the microcirculatory values at the time of admission to PICU [19]. E-selectin, ICAM-1 and VCAM-1 were increased in both early and late pediatric sepsis [20], whereas meningococcal septic shock was associated with a significant and persistent increase in circulating soluble co-inhibitory immune receptor carcinoembryonic antigen-related cell-adhesion molecule 1 concentration from 24-48 h up to day 7-8 following PICU admission [21].…”
mentioning
confidence: 88%